DAMPAK MEDIA SOSIAL TERHADAP SIKAP DAN PERILAKU MASYARAKAT TENTANG KESEHATAN - Sonia Regina Putri (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Social media has become an inseparable part of modern society, influencing various aspects of life, including people's attitudes and behavior regarding health. The research method used uses data collection techniques through in-depth interviews. Research subjects are individuals who actively use social media to obtain information about health. This research aims to explore in depth the impact of social media on people's attitudes and behavior regarding health. The research results show that social media has a complex impact on people's attitudes and behavior regarding health. On the one hand, social media can be a useful platform for increasing awareness, education and access to health information. On the other hand, social media can also be a source of false and misleading information, which can have negative consequences for an individual's mental and physical health. Through in-depth qualitative analysis, this research will try to understand how social media influences the way people view health, how information spread on social media influences their health decisions, and how social media literacy can moderate this influence.